Effect of Vestibular Telerehabilitation in Motion Sickness Among Healthy Individuals- A Randomized Control Trial - Priyanka Nahak,; Sonali Soumyashree,; Soumya Ranjan Lenka,; B. Maithili Dutta Pradhan, (The Bioscan, 2025)
Background Motion sickness encompasses a group of symptoms that arise due to actual or perceived motion of an individual or their environment. This can induce a stress response resulting in various autonomic manifestations. Vestibular therapy enhances both static and dynamic balance by utilizing the brain's neuroplasticity. Telerehabilitation is a modern approach that extends therapeutic services beyond conventional clinical settings using digital platforms. Objective This study aimed to find the impact of vestibular telerehabilitation on motion sickness in healthy adult individuals. Methods 42 healthy individuals between the ages of 18 and 40 were split into two groups at random: Group A (experimental group, n = 21) and Group B (control group, n = 21). Over the course of six weeks, the intervention plan called for twice-daily, five-minute sessions. The Motion Sickness Assessment Questionnaire (MSAQ), the Misery Scale (MISC), and the Motion Sensitivity Quotient (MSQ) were used to measure motion sickness symptoms both before and after the intervention. Results Motion sickness symptoms were shown to have decreased statistically significantly (p<0.05) in the experimental group following six weeks of vestibular telerehabilitation. Comparative analysis between the groups revealed that Group A experienced significantly greater improvement (p<0.05) than Group B. Conclusion According to the study's findings, vestibular telerehabilitation is a useful and successful strategy for lowering motion sickness symptoms in healthy people.